The Colleration Between Da'wah Programme and Electronic Media: A Case Study at RTM - Mohd Sayuti Bin Rani (Kolej Universiti Islam Malaysia, 2011)
In the fast-pace development nowadays, mass media as a great influence in our daily life. Mass media indirectly has either positive or negative impact to the society. In response to this project paper, electronic media particularly television channel is a significant medium in disseminating information and message among society. As we could see at the present the national television channel such as TV 1, TV 2, TV 3, NTV 7 Channel 9 and TV 8 are increasingly competing among themselves to broadcast compelling programmes beyond the boundary of religion and culture. Consequently, the religious programmes seems to be dissented and neglected compare to others especially entertainment programme. Pertaining to this matter, the correlation between da'wah (Islamic mission) programme and electronic media a case study at RTM outstanding combination in which may effect the ongoing situation, the more effective da'wah programme at RTM, the more effective of RTM channel is. For this purpose, this project paper has distributed 100 questionnaires around Pandan Indah, Kuala Lumpur. While, for the methodology applied in this research, two different kinds of methods have been adopted like library and field study.